Development strategy for small and medium-scale halal food and beveragesector in Indonesia - Rosadi, Chodijah Puteri; Nursyamsiah, Tita (Halal Studies and Society, 2024)
Indonesia, with the world’s largest Muslim population, is the leading consumer of halal food and beverage.Despite its substantial consumer base, the country has not been able to capitalize on this demand to increasethe production of halal products. Therefore, this study aimed to identify strengths, weaknesses, opportunities,and threats (SWOT) facing halal food and beverage small and medium enterprises (SMEs) in Indonesia anddevelop growth strategies. The study procedures used Analytic Network Process (ANP) method combined withSWOT network structure to evaluate the factors affecting the sector. The results showed that the most significantstrength was the merger of food science with Islamic principles, while the primary weakness identified was theinsufficient financing and investment available to sector participants. Government backing had also become themost significant opportunity, while the most significant threat was the volatility of global economic conditions. Basedon these results, the strategic priority identified for advancing Indonesian halal food and beverage SEMs was overalldevelopment.